KPIs for performance measurement of e-fulfillment systems in multi-channel retailing: An exploratory study. Issue 1 (23rd September 2019) - Bressolles, Gregory; Lang, Gerald
Abstract : Purpose: The purpose of this paper is to expand existing research on fulfillment systems for multi-channel retailers by combining analysis of customer expectation (CE) with economic performance (EP) aspects. Design/methodology/approach: This exploratory study is based on a literature review of supply chain management and marketing combined with the results of an online questionnaire submitted to French and Chinese multi-channel retailers from two sectors. Findings: The results enable the authors to identify 13 important key performance indicators (KPIs) used by multi-channel retailers for measuring e-fulfillment system performance and also to determine under which of the EP or CE criteria these KPIs might be linked. Research limitations/implications: Although the sample size is limited, this research is intended to be exploratory, based on the practices of supply chain and marketing managers. Moreover, the results do not address interdependencies among the different KPIs. Practical implications: E-fulfillment is a major challenge for multi-channel retailers; it is cost intensive and critical for customer satisfaction. The identified set of KPIs enables retailers to choose those relevant to their particular infrastructure. Originality/value: A limited number of scholarly works have explored the operational implications of online retailing in terms of e-fulfillment in a multi-channel context. In order to manage such supply chains efficiently and effectively, traditional measures of supply chain performance need to be adapted. This study expands existing knowledge by developing measurement systems and metrics for the evaluation of supply chain performance in this context.